Endovascular Therapy Is Effective for Leriche Syndrome with Deep Vein Thrombosis - Tasuku Higashihara; Nobuo Shiode; Tomoharu Kawase; Hiromichi Tamekiyo; Masaya Otsuka; Tomokazu Okimoto; Yasuhiko Hayashi (Case Reports in Cardiology)
A 65-year-old man presented to our hospital due to intermittent claudication and swelling in his left leg. He had Leriche syndrome and deep vein thrombosis. We performed endovascular therapy (EVT) for Leriche syndrome, and a temporary filter was inserted in the inferior vena cava. He received anticoagulation therapy for deep vein thrombosis. The stenotic lesion in the terminal aorta was stented with an excellent postprocedural angiographic result and dramatic clinical improvement after EVT. This case suggests that EVT can be a treatment for Leriche syndrome.